IRFOC induction motor with rotor time constant estimation modelling and simulation - Radwan, E.; Mariun, N.; Aris, I.; Bash, S. M.; Yatim, Abdul Halim Mohamad (Emerald Group Publishing Limited, 2005)
Purpose– To provide a new and simple inverse rotor time constant identification method which can be used to update an indirect rotor field oriented controlled (IRFOC) induction motor algorithm.Design/methodology/approach– Two different equations are used to estimate the rotor flux in the stator reference frame. One of the equations is a function of the rotor time constant, rotor angular velocity and the stator currents. The other equation is a function of measured stator currents and voltages. The equation that uses the voltage and the current signals of the stator serves as reference model, however, the other equation works as an adjustable model with respect to the variation of the rotor time constant. Voltage signals used in the reference model equation are obtained from the measured DC bus voltage and the inverter gating signals. The proposed scheme is verified using a MATLAB/SIMULINK model for two different motors and experimentally using a DSP development tool (MCK 243) supplied by Technosoft S.A.Findings– The proposed estimator was able to successfully track the actual value of the inverse rotor time constant for different load torque and speed operating conditions. Increased oscillations in the estimated inverse rotor time constant appeared at lower speeds (below 10 per cent of rated speed) due to drift in a PI regulator (used at the estimator side), which was tuned under rated operating conditions and using parameters nominal values.Research limitations/implications– This estimation scheme is limited when near zero speed operation is demanded; otherwise it gives a simple and practical solution. A suggested way out of this, is to provide a self‐tuning controller that can automatically adjust even for zero speed operation, or to automatically disconnect the estimator and take the most updated value as long as the operating speed is below a predetermined value.Originality/value– This paper presented a new inverse rotor time constant estimator for an IRFOC induction motor application and in conjunction rotor flux was estimated without voltage phase sensors.